2020
DOI: 10.3390/plants9030399
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Applied Fertilization Method under Full Straw Return on the Growth of Mechanically Transplanted Rice

Abstract: This study aimed to improve nitrogen utilization and alleviate the inhibition of straw decomposition during early tillering and the growth of paddy after straw return. Specifically, three different nitrogen fertilizer (base fertilizer) application methods were tested under full straw return: applying the compound fertilizer once (J1), applying the compound fertilizer twice (J3) and applying the ammonium carbonate fertilizer plus compound fertilizer (J2). Full straw return without fertilizer (CK1) and no straw … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…Compared with compound fertilizer (S0 treatment), the ammonium bicarbonate combined with compound fertilizer was a more effective fertilization method for straw decomposition. Their result was similar to previous research (Tang et al, 2020). Compared with previous reports (Takakai et al, 2018; Agustina et al, 2019), this present study not only provided a nitrogen application method that was conducive to straw decomposition, but also analyzed the correlation between ammonium nitrogen fertilizer and straw decomposition through regression model.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Compared with compound fertilizer (S0 treatment), the ammonium bicarbonate combined with compound fertilizer was a more effective fertilization method for straw decomposition. Their result was similar to previous research (Tang et al, 2020). Compared with previous reports (Takakai et al, 2018; Agustina et al, 2019), this present study not only provided a nitrogen application method that was conducive to straw decomposition, but also analyzed the correlation between ammonium nitrogen fertilizer and straw decomposition through regression model.…”
Section: Discussionsupporting
confidence: 93%
“…This characteristic indicates that ammonium N fertilizer as a base fertilizer may be able to quickly provide N nutrients for the decomposition of straw and the early growth of plants. To solve these problems, ammonium N fertilizer and compound fertilizer were used as the base fertilizer after returning straw to field (Tang et al, 2020), so as to promote the decomposition rate of straw, improve the tillering and dry matter accumulation of rice during early growth period. However, the combined application method may also lead to a later nutrient deficiency and a decline in grain yield, probably because the high ratio of ammonium N fertilizer in the base fertilizer could cause rapid nutrients loss.…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed that N fertilizer reduction increased fertilizer use efficiency . Combining application with straw returning would help improve N efficiency, thereby achieving higher stable yields. ,, The straw returning improved soil condition which favored fertilizer adsorption from the soil . It was reported that wheat straw return increased the rice yields by 2.11–4.28% and also improved dry matter accumulation and N utilization .…”
Section: Resultsmentioning
confidence: 99%
“…Straw is rich in a large number of carbon elements, and its C/N ratio is much higher than the suitable range of soil microorganisms. In addition, microorganisms will consume a certain amount of nitrogen during the decomposition of straw, which will lead to the reduction of nitrogen in the soil and fail to meet the normal growth of rice in the early stage ( Tang et al., 2020 ). Pei et al.…”
Section: Discussionmentioning
confidence: 99%